The Migration of Hungarian Refugees to Prince Edward Island, Canada (1956-1957) – A Communicative Inquiry With a Local Newspaper - Bobby Thomas Cameron (KOME: An International Journal of Pure Communication Inquiry)
This article describes how local media in the smallest province of Canada socially constructed the arrival of Hungarian refugees on Prince Edward Island (PEI), Canada from 1956-1957. This article addresses the role which the media has in the social construction of refugees, as well as sheds light on the niche topic of refugee migration to Prince Edward Island in the late 1950s. From an analysis of newspaper articles from The Guardian (PEI) it was found that during 1956-1957 Hungarian refugees were positively received on Prince Edward Island because they were anti-soviet political symbols. This political factor, coupled with their perceived ability to contribute to the Island’s economy, encouraged their positive reception. The article argues that using newspapers as a primary source in a historical study of immigration can uncover both explicit and implicit attitudes with regards to communication, culture, and society.